How are MCPIP1 and cytokines mutually regulated in cancer-related immunity? - Ruyi Xu; Yi Li; Yang Liu; Jianwei Qu; Wen Cao; Enfan Zhang; Jingsong He; Zhen Cai (Protein & Cell, 2020)
Abstract Cytokines are secreted by various cell types and act as critical mediators in many physiological processes, including immune response and tumor progression. Cytokines production is precisely and timely regulated by multiple mechanisms at different levels, ranging from transcriptional to post-transcriptional and posttranslational processes. Monocyte chemoattractant protein-1 induced protein 1 (MCPIP1), a potent immunosuppressive protein, was first described as a transcription factor in monocytes treated with monocyte chemoattractant protein-1 (MCP-1) and subsequently found to possess intrinsic RNase and deubiquitinase activities. MCPIP1 tightly regulates cytokines expression via various functions. Furthermore, cytokines such as interleukin 1 beta (IL-1B) and MCP-1 and inflammatory cytokines inducer lipopolysaccharide (LPS) strongly induce MCPIP1 expression. Mutually regulated MCPIP1 and cytokines form a complicated network in the tumor environment. In this review, we summarize how MCPIP1 and cytokines reciprocally interact and elucidate the effect of the network formed by these components in cancer-related immunity with aim of exploring potential clinical benefits of their mutual regulation.